Case Report: Ectopic Adrenocortical Carcinoma in the Ovary - Tsai, Wen-Hsuan; Chen, Tze-Chien; Dai, Shuen-Han; Zeng, Yi-Hong (Frontiers in Endocrinology, 2021)
Adrenocortical carcinoma (ACC) is a rare malignancy with an incidence of 0.7–2.0 cases/million habitants/year. ACCs are rare and usually endocrinologically functional. We present the case of a 59-year-old woman who experienced abdominal fullness for 6 months and increased abdominal circumference. A large pelvic tumour was observed. She underwent cytoreductive surgery and the pathological test results revealed local tumour necrosis and prominent lympho-vascular invasion. Neuroendocrine carcinoma was the first impression, but positivity for synaptophysin, alpha-inhibin, transcription factor enhancer 3 (TFE-3), calretinin (focal), and CD56 (focal) and high Ki-67-labeling proliferating index (>80%) confirmed the diagnosis of ectopic ACC. Ectopic primary aldosteronism could not be excluded. However, we did not perform saline infusion test or captopril test due to poor performance status. When pathological test reports reveal neuroendocrine features not typically found in the organ being examined, IHC staining should be performed to rule out ectopic ACC. Whether the ectopic ACC is functional or not requires complete survey.